Price personalization in the Big Data and GDPR context - Rekettye, Gábor; Pranjić, Goran (Marketing & Menedzsment, 2020)
THE AIM OF THE PAPER This study intends to discuss a rather newly observable fact in management practice that is the personalization of pricing. The possibility of this phenomenon is brought up by the rapid industrial development called by scientists and practitioners the fourth industrial revolution. METHODOLOGY It is a conceptual paper based not on the results of particular field research. Its methodology is grounded on desk research, which contained the review of the scientific literature and observations of research institutions analyzing the practical development going on nowadays in the different fields of the economy. MOST IMPORTANT RESULTS The study proves that as a result of the fourth industrial revolution, the elbowroom of pricing is growing. The growing zone for price-setting makes it necessary for companies to use new and more sophisticated methods among them price personalization. Personalization requires lots of information about the individual behavior of customers. The advanced analytics of Big Data can deliver real-time information; however, if they are used without control, the privacy of customers may become hurt. The paper discusses the effects of the General Data Protection Rules (GDPR) on companies and customers. RECOMMENDATIONS The paper concludes that price personalization, which is a kind of price discrimination, should be used by sellers with care. The effects of GDPR will be not limited to the European Union; it will have worldwide consequences. Acknowledgements: The earlier version of this paper was submitted and accepted for presentation to the 11th International Odyssey Conference on Economics and Business organized by the FEB, University of Zagreb 2020.